2012
DOI: 10.4490/algae.2012.27.1.009
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in kelp phlorotannins in relation to grazer abundance and environmental variables in the Alaskan sublittoral zone

Abstract: Phlorotannins are common metabolites produced in kelps that can have deterrent functions against grazers. The factors dictating seasonal patterns of phlorotannin content in northeastern Pacific kelps are not well understood. This study assessed density and grazing of the gastropod Lacuna vincta on the annual canopy-forming kelp Nereocystis luetkeana and the perennial understory species Agarum clathratum, Saccharina latissima and S. groenlandica in Kachemak Bay, Alaska. In addition, we assessed seasonal pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 71 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…For all grazing experiments, 8 Lacuna (~2 mm) were added to each vessel. The number of Lacuna used mimicked densities found on Ulva assemblages at the collection site (0.5−1 grazer cm −2 ) and reported in the literature (Chenelot & Konar 2007, Dubois & Iken 2012.…”
Section: Preparation Of Experimentsmentioning
confidence: 86%
“…For all grazing experiments, 8 Lacuna (~2 mm) were added to each vessel. The number of Lacuna used mimicked densities found on Ulva assemblages at the collection site (0.5−1 grazer cm −2 ) and reported in the literature (Chenelot & Konar 2007, Dubois & Iken 2012.…”
Section: Preparation Of Experimentsmentioning
confidence: 86%
“…It has been suggested that macro-and micro-topographically uniform smooth blades of large kelps may not be a preferred attachment surface for many diatom taxa [8,13,49], while epithelial cell sloughing that is most likely common in long-lived kelps [18,19,21] would effectively limit the number of diatoms developing on the thallus. Moreover, production of secondary metabolites is used by various kelp species to deter herbivores [53][54][55]. However, the bioactive compounds excreted by macroalgae may affect not only grazers but also the microalgal biofoulers-both directly and indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the amount of U. rigida used in experiments (∼8 -9 cm 2 per sample), the appropriate number of L. vincta was added. The number of L. vincta used mimicked densities found on U. rigida at the collection site (0.5 -1 grazer cm −2 ) and reported in the literature (Chenelot and Konar, 2007;Dubois and Iken, 2012;Young et al, 2019).…”
Section: Preparation Of Experimentsmentioning
confidence: 91%